Oral health in residential aged care: Perceptions of nurses and management staff. Issue 2 (13th November 2019) - Patterson Norrie, Tiffany; Villarosa, Amy R.; Kong, Ariana C.; Clark, Sally; Macdonald, Susan; Srinivas, Ravi; Anlezark, Jennifer; George, Ajesh
Abstract: Aim: This study aimed to explore the perceptions of residential aged care nursing and management staff regarding oral care, to develop strategies to improve the oral health of aged care residents. Design: A qualitative approach was used. Methods: Two focus groups were conducted with nursing and management staff at two residential aged care facilities and transcripts were thematically analysed. Results: All staff had an awareness of the importance of oral health; however, they highlighted the significant challenges in the current system that affect implementation of oral health training and practice guidelines in the residential aged care facility. High staff turnover, time constraints, difficulties in accessing dental services and working together with residents, their families and external staff were barriers to providing oral health care. Staff highlighted the need for formalized clinical guidelines and processes and efficient dental referral pathways to create a more cohesive system of care.